MENGHIDUPKAN TRADISI DAN KEBUDAYAAN JAWA DALAM KRISTENISASI KIAI SADRACH DI PURWOREJO JAWA TENGAH - Muhammad Nur Rosyid Huda Setiawan; Muttaqin muttaqin; Naufal Ulya (Al Hikmah, 2022)
This article discusses the Christianization carried out by Kiai Sadrach by reviving Javanese traditions and culture in the Purworejo area, Central Java. Javanese society is a society that is known to be thick with the problems of tradition and culture in it. Until now, Javanese traditions and culture still dominate in giving color to the diversity of state life in Indonesia. In the nineteenth century western missionaries began to spread the teachings of Christianity, but were considered a failure in their movement because they did not want to compromise with local traditions and culture. So that the Javanese people find it difficult to accept these teachings. So Kiai Sadrach emerged as a propagator of Christianity from the indigenous group. The purpose of this research is to scientifically examine the discussion of Javanese traditional methods and culture in the Christianization that was brought to life by Kiai Sadrach in Purworejo, Central Java, in terms of worship and social relations in the environment. In the process of collecting data, using library research and using two methods. The first is descriptive method, which is to explain and explain Javanese traditions and culture. The second method is historical, namely explaining the Christianization movement carried out by Kiai Sadrach during the Dutch colonial period. In this case, the researcher found that there was a method in reviving Javanese tradition and culture in the teachings of Christianity which was spread by Kiai Sadrach to the Javanese community. The first method is found in the pattern of Christian worship. Then the second method is found in the pattern of social relations in the environment.